FAKTOR IBU DENGAN RIWAYAT OBSTETRI PADA PERSALINAN OPERASI SESAR DI JAKARTA - Cicih, Lilis Heri Mis; Mursyid, Nurmawati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
The high rate of deliveries by caesarean section in urban areas is a problem. With BPJS membership, now cesarean delivery can be done, so that the number is increasing. The aim of the study was to determine the dominant maternal factors for cesarean delivery. This type of research is retrospective quantitative. The sample size was 140 respondents and was randomly selected from a population of 238 patients in 2018. Data sourced from patient medical records were analyzed univariately to assess their distribution, bivariate with chi square test, and multivariate with multiple logistic regression analysis. The results of the bivariate analysis found the relationship between cesarean delivery with maternal age (p-value 0.031), the incidence of premature rupture of membranes (p-value 0.032), and obstetric history (p-value 0.008). Apart from that, there was no association between cesarean delivery and parity (p-value 0.274), gestational distance (p-value 0.361), hypertension (p-value 0.586), asthma (p-value 0.366), and diabetes (p-value 1,000). The results of the multivariate analysis found that obstetric history was the dominant variable, giving a 3 (three) times higher chance of having a cesarean delivery. For the maternal age and the incidence of premature rupture of membranes have 2 (two) times higher chance of having a cesarean delivery. Recommendations for the Ministry of Health and its staff to strengthen reproductive health education policies from an early age, namely when women menarch, through mandatory learning at every level of education.